Estimated aerobic power, muscular strength and flexibility in elite Brazilian Jiu-Jitsu athletes - Vidal Andreato, L.; Franzoi de Moraes, S. M.; Lopes de Moraes Gomes, T.; Del Conti Esteves, J. V.; Vidal Andreato, T.; Franchini, E. (Science & Sports, 2011)
Objective This study was designed to estimate the maximum oxygen uptake, muscular strength and flexibility of elite Brazilian Jiu-Jitsu athletes. Methods The sample consisted of eleven Brazilian Jiu-Jitsu athletes (25.8 ± 3.3 years old) who were medallists at national and/or international competitions. The aerobic power was estimated by a treadmill test, according to the Bruce Protocol. The maximal isometric strength (hand, leg and back) was measured by specific dynamometric tests. We used sit-ups and push-ups to evaluate abdominal and upper limb strength endurance, respectively. We applied the sit-and-reach test to determine hip, back and posterior flexibility of the muscles of the lower limbs. Results We observed a VO2max of 49.4 ± 3.6 mL/kg per minute for the treadmill test. We observed measures of 43.7 ± 4.8 kgf for the right maximal isometric handgrip strength, 40.1 ± 3.8 kgf for the left maximal isometric handgrip strength, 185.5 ± 36.0 kgf for the maximal isometric back strength and 154.3 ± 41.9 kgf for the maximal isometric leg strength. In the strength endurance test, the athletes performed 52 ± 7 repetitions in a 1-min sit-up test, and 40 ± 8 repetitions in the push-up test. In the sit-and-reach test, the athletes had an average score of 36 ± 9 cm. Conclusions The elite Brazilian Jiu-Jitsu athletes had medium aerobic power and flexibility, excellent abdominal and upper body strength endurance and maximal isometric back strength. However, these athletes did not have high maximal isometric handgrip or leg strength.